A new species of the genus Xya Latreille, 1809 from Shandong, China (Orthoptra, Tridctyloidea, Tridactylidae) - Zhang, Da-Peng; Yin, Hai-Xiang; Yin, Zhan (Zootaxa, 2018)
The genus Xya Latreille, 1808 obtains 56 known species in the world, among them 20 species distributed in Asia and 7 species in China only i.e. Xya japonica (Haan, 1842); Xya nitobei (Shiraki, 1911); Xya manchurei Shiraki, 1936; Xya apicicornis (Chopard, 1928); Xya riparia (Saussure, 1877); Xya leshanensis Cao et al, 2017 and Xya sichuanensis Cao et al, 2018, [Haan, 1844; Walker, 1871; Saussure, 1877, 1896; Brunner von Wattenwyl. 1893; Bolivar, 1900(1899); Shiraki, 1911, 1936; Chopard, 1928, 1936, 1968; Bey-Bienko, 1967; Günther, 1974. 1980; Ingrisch, 1987; Yin et al, 1996; Murai, 2005; Yin et al, 2013; Heads & Hollier, 2016; Kuravova & Kocarek, 2016; Zhang et al, 2017; Cao et al, 2017; Cao et al, 2018; Cigliano et al, 2018]. In the present paper, we describe a new species of the genus from Junan county, Shandong province, China. The new species Xya shandongensis sp. nov. is similar to Xya japonica (Haan, 1842), but differs from latter by antennae near moniliform, length of segment 1.2 times maximum width, median and lateral ocelli placed median part of eyes, pronotum with larger yellow stripe on hind apical part of both sides, hind femur black, upper side with a yellowish-white spot at the base of 1/3 place, hind wing long, reaching the base of epiproct. Type specimens are deposited in the College of Plant Protection, Shandong Agricultural University, Taian, Shandong 271018, China.